Pengaruh Service Recovery terhadap Customer Satisfaction pada Hotel Royal Jember - Luccy Avrindy Ragilia Putri; Bambang Irawan; Elok Sri Utami (Jurnal Ekonomi Akuntansi dan Manajemen, 2019)
This article aims to determine the effect of service recovery consisting of procedural justice, interactional justice and distributive justice on customer satisfaction in guests Hotel Royal Jember. Methods of data collection is done by distributing questionnaires to 104 respondents who are guests Hotel Royal Jember with the following criteria must be at least 17 years because they have had the income and memampu use the services of the hotel and was the guest of Hotel Royal Jember ever experienced keluihan when using the services of Hotel Royal Jember , The data used in this study are primary data and secondary data. The data analysis method used is logistic regression analysis. The results showed that the variables used are service recovery consisting of procedural justice, interactional justice and distributive justice effect on customer satisfaction in guests Hotel Royal Jember Keywords: Distributive Justice, Interactional Justice, Procedural Justice, Customer Satisfaction.